The EARLY trials: a consortium of studies targeting weight control in young adults. Issue 3 (28th January 2014) - Lytle, Leslie A; Svetkey, Laura P; Patrick, Kevin; Belle, Steven H; Fernandez, I Diana; Jakicic, John M; Johnson, Karen C; Olson, Christine M; Tate, Deborah F; Wing, Rena; Loria, Catherine M
Abstract: Young adulthood has been identified as a high-risk period for the development of obesity but few interventions have been tested in this population. One way to escalate our learning about effective interventions is to test a number of interventions simultaneously as a consortium of research trials. This paper describes the Early Adult Reduction of weight through LifestYle intervention (EARLY) trials. Seven research sites were funded to conduct intervention trials, agreeing to test similar primary outcomes and cooperating to use a set of common measurement tools. The EARLY consortium was able to work cooperatively using an executive committee, a steering committee, workgroups and subcommittees to help direct the common work and implement a set of common protocol and measurement tools for seven independent but coordinated weight-related intervention trials. Using a consortium of studies to help young adults reach or maintain a healthy weight will result in increased efficiency and speed in understanding the most effective intervention strategies.